2003
DOI: 10.1046/j.1365-2133.2003.05407.x
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate inhibits proliferation and regulation of the expression of intercellular adhesion molecule-1 and vascular cell adhesion molecule-1 by cultured human umbilical vein endothelial cells

Abstract: Low-dose MTX may act on psoriasis by suppressing the TNF-alpha-induced expression of ICAM-1 and VCAM-1 by vascular endothelial cells. Inhibition of neovascularization may be another mechanism of action of MTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 43 publications
(42 reference statements)
2
32
0
Order By: Relevance
“…Several studies have reported the inhibitory effect on ICAM-1 expression by MTX (13,24,36,37), although the mechanisms of the inhibition of ICAM-1 by MTX are unclear. Expression of ICAM-1 can be induced by a variety of factors, including inflammatory cytokines, reactive oxygen species, and shear stress (7,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the inhibitory effect on ICAM-1 expression by MTX (13,24,36,37), although the mechanisms of the inhibition of ICAM-1 by MTX are unclear. Expression of ICAM-1 can be induced by a variety of factors, including inflammatory cytokines, reactive oxygen species, and shear stress (7,38).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the hyperglycemic effects, we used the agents of d-glucose (Sigma, St. Louis, MO). Confluent cultures of HUVEC in 100-mm dishes were preincubated with or without 10 mM MTX for 2 h or 10 mM lactacystin for 1 h. The effective concentrations of MTX and lactacystin were decided on the basis of published data (22)(23)(24) and our own preliminary study. After preincubation of MTX or lactacystin, they were added to 24.5 mM d-glucose (high glucose [HG]) and incubated for 24 h. After incubation, cells were collected using a cell scraper and were lysed in TNE Buffer (50 mM Tris-HCl [pH 7.4], 1% Nonidet P-40, and 20 mM EDTA) for 30 min on ice.…”
Section: Effect Of Mtx and Lactacystin For Hg-induced Icam-1 Expressimentioning
confidence: 99%
“…In previously reported studies, for normal endothelial cells (HUVEC), 1 µM 2ME2 showed no appreciable toxicity, 32 while MTX at this same concentration exhibited significant cytotoxicity. 33 The previous study 34 showed that proliferation and apoptosis of normal lymphocytes was not altered significantly, even at higher doses (3-20 µM) of 2ME2. In contrast, our results have shown that proliferation and apoptosis of lymphoma cells were dose-dependant responses to 2ME2.…”
Section: Discussionmentioning
confidence: 96%
“…The present model, methotrexate inhibited CD11a expression at 4 and 48 h after pleurisy induction and CD18 at 4 h after. Yamasaki et al (2003) showed that methotrexate inhibited ICAM-1 and VCAM-1 in cultured human umbilical vein endothelial cells. Other studies have reported that methotrexate significantly decreased the E-selectin, ICAM-1 and VCAM-1 levels in bullous pemphigoid patients (Dahlman-Ghozlan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%